Réponses

2013-05-03T17:09:03+02:00

a.

 

4(x + 5) = 10x + 3

4*x+4*5=10x+3

4x+20=10x+3

4x-10x=3-20

-6x=-17

x=-17/-6

x=17/6

 

b.

 

3(x – 2) = 6(x + 4)

3*x+3*(-2)=6*x+6*4

3x-6=6x+24

3x-6x=24+6

-3x=30

x=30/-3

x=-10

 

c.

 

7x – (5x + 3) = 5(x – 3) + 2

7x-5x-3=5*x+5*(-3)+2

2x-3=5x-15+2

2x-5x=-15+2+3

-3x=-10

x=-10/-3

x=10/3

 

d.

 

7(n + 2) – 3 = 25 – (3n + 4)

7*n+7*2-3=25-3n-4

7n+14-3=25-3n-4

7n+3n=25-4-14+3

10n=10

n=10/10

n=1

 

e.

 

4y + 3(4y – 2) = 3(y + 1)

4y+3*4y+3*(-2)=3*y+3*1

4y+12y-6=3y+3

4y+12y-3y=3+6

13y=9

y=9/13

 

 

2013-05-03T17:09:26+02:00
A) 4(x+5)=10x+3
4x+20=10x+3
17=6x
x=17/6

b) 3(x-2)=6(x+4)
3x-6=6x+24
-30=3x
x=-30/3=-10

c) 7x-(5x+3)=5(x-3)+2
7x-5x-3=5x-15+2
2x-3=5x-13
10=3x
x=10/3

d) 7(n+2)-3=25-(3n+4)
7n+14-3=25-3n-4
7n+11=21-3n
10n=10
n=10/10=1

e) 4y+3(4y-2)=3(y+1)
4y+12y-6=3y+3
16y-6=3y+3
13y=9
y=9/13